Update on atmospheric neutrinos - Gonzalez-Garcia, M. C. [UNESP]; Nunokawa, H.; Peres, O. L G; Stanev, T.; Valle, J. W F (American Physical Society (APS), 1998)
We discuss the impact of recent experimental results on the determination of atmospheric neutrino oscillation parameters. We use all published results on atmospheric neutrinos, including the preliminary large statistics data of Super-Kamiokande. We reanalyze the data in terms of both vμ → vτ and vμ → ve channels using new improved calculations of the atmospheric neutrino flux. We compare the sensitivity attained in atmospheric neutrino experiments with those of accelerator and reactor neutrino oscillation searches, including the recent CHOOZ experiment. We briefly comment on the implications of atmospheric neutrino data in relation to future searches for neutrino oscillations with long baselines, such as the K2K, MINOS, ICARUS, and NOE experiments.